PENILAIAN KEPUTUSAN INVESTIGASI VARIAN: EFEK OUTCOMES DAN FRAMING - Handoko, Jesica (Jurnal Akuntansi Kontemporer, 2010)
Performance appraisal involves the judgmental evaluation, that should be made by performance appraiser on the basis of valid and reliable evidence, including when he/she evaluates his/her subordinate (a decision maker) who made variance investigation decision. It predict: (I) Outcome bias will have an impact on the perceived benefit of the investigation, (2) investigation expenditures matched with perceived benefit are framed as costs while those without perceived benefit are framed as losses, and (3) evaluators with a cost frame provide higher performance ratings than those with a loss frame. An laboratory experiment design, with one hundred and ninety one Cost Accounting students demonstrates that outcome effect affect performance appraisal significantly. When managers did not investigate cost variance, they were evaluated more unfavorably when investigation revealed problems in the system. Further, the investigation outcome affect the perceived benefit of the investigation signifzcantly, expenditures with perceived benefit are framed as costs while those without perceived benefit are framed as losses. Thus, paying premium frame in this research conclude moderately signifzcantframing effect on higher performance.